A Bottom‐Up Approach to Build 3D Architectures from Nanosheets for Superior Lithium Storage. (25th June 2013) - Gong, Yongji; Yang, Shubin; Zhan, Liang; Ma, Lulu; Vajtai, Robert; Ajayan, Pulickel M.
<x xml:space="preserve">Abstract</x> Two‐dimensional (2D) atomic layers such as graphene, and metal chalcogenides have recently attracted tremendous attention due to their unique properties and potential applications. Unfortunately, in most cases, the free‐standing nanosheets easily re‐stack due to their van der Waals forces, and lose the advantages of their separated atomic layer state. Here, a bottom‐up approach is developed to build three‐dimensional (3D) architectures by 2D nanosheets such as MoS2 and graphene oxide nanosheets as building blocks, the thin nature of which can be well retained. After simply chemical reduction, the resulting 3D MoS2‐graphene architectures possess high surface area, porous structure, thin walls and high electrical conductivity. Such unique features are favorable for the rapid diffusions of both lithium ions and electrons during lithium storage. As a consequence, MoS2‐graphene electrodes exhibit high reversible capacity of ≈1200 mAh g−1, with very good cycling performance. Moreover, such a simple and low‐cost assembly protocol can provide a new pathway for the large‐scale production of various functional 3D architectures for energy storage and conversions.